2016
DOI: 10.1007/s40097-016-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm activity of biogenic copper and zinc oxide nanoparticles-antimicrobials collegiate against multiple drug resistant bacteria: a nanoscale approach

Abstract: The synthesis of biogenic nanoparticles from non-chemical resources has increased the drive toward understanding infection biology. Accordingly, we aimed to address the symbiotic antibiofilm effect of biogenic copper and zinc oxide nanoparticles with antimicrobials against multidrug resistant (MDR) pathogens. The minimum inhibitory concentration (MIC) of copper nanoparticles (CuNPs) and zinc oxide nanoparticles (ZnONPs) at the range from 2 to 128 lg/ml was calculated against Grampositive and Gram-negative path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 34 publications
(34 reference statements)
1
44
0
Order By: Relevance
“…The exopolysaccharide (the principal precursors of biolm production) formation was hindered so C. albicans could not produce a biolm. 28 Our anti-biolm research is comparable to the ndings of Ashajyothi et al, 50 who stated that the synthesized ZnO NPs displayed a biolm hindrance% of 10.7% against P. aeruginosa following 18 h incubation.…”
Section: Mapping Analysis Of the Elements In Bisupporting
confidence: 85%
See 1 more Smart Citation
“…The exopolysaccharide (the principal precursors of biolm production) formation was hindered so C. albicans could not produce a biolm. 28 Our anti-biolm research is comparable to the ndings of Ashajyothi et al, 50 who stated that the synthesized ZnO NPs displayed a biolm hindrance% of 10.7% against P. aeruginosa following 18 h incubation.…”
Section: Mapping Analysis Of the Elements In Bisupporting
confidence: 85%
“…The synthesized Bi 2 O 3 NPs-Nystatin was applied to repress biolm development in its constant adhesion step (also iden-tied as the primary stage). 50 However, the mechanistic behavior of the incorporated Bi 2 O 3 NPs upon biolm development has yet to be conrmed.…”
Section: Mapping Analysis Of the Elements In Bimentioning
confidence: 99%
“…This partial effect directly from copper nanoparticles may imply the direct interaction of nanoparticles with efflux pumps, supporting the first hypothesis, while partial effect due to release of Cu(II) ions might indicate the disruption of membrane potential and perturbing working of efflux pumps, supporting the second hypothesis [9]. Chatterjee et al have also revealed the loss of membrane potential of E. coli cells from −185 to −105 and −75 mV after growing bacterial cells in the presence of 3.0 and 7.5 μg/ml concentration of copper nanoparticles, respectively, for 1 h [22].…”
Section: Nanoparticles As Efflux Pump Inhibitorsmentioning
confidence: 67%
“…Based on several research papers, ZnO-NPs of particle sizes less than 37 nm were successfully synthesized in temperatures lower than 500 C [38]. MIC value for these ZnO-NPs against E. coli and E. faecalis were reported to be 32 mg/mL and 16 mg/mL, respectively [42]. Smaller sizes of ZnO-NPs produce lower MIC value as compared to bigger-sized ZnO-NPs.…”
Section: Evaluation Of Antibacterial Effects Of P Granatum/zno-npsmentioning
confidence: 99%